Scalability in Indigenous Queer Futurism: Eco-Spiritual Healing in the Young Adult Dystopian Novel The Marrow Thieves - Bradley, Monica (2025)
This paper applies a queer indigenous reading of the concept of scalability in the novel The Marrow Thieves in consideration of the telling of Story, the oral story-telling tradition of climate change, residential schools, Native American history, and the healing power of dreams in eco-spirituality, as told from the perspective of the queer/Two-Spirit Elder, Miigwan. It unearths some matters of space and time within the novel in the role of Native American residential schools, climate change, indigenous history and eco-spirituality in a scalable queer speculative future by demonstrating the inseparability of time (present/past/future), space (the local/national/global/cosmic) and matter (physical/metaphysical/spiritual) to provide both a warning and hope for the future. The paper argues that the novel scales Indigenous dystopian lived and imagined hauntings without falling into a fatalistic trap that many non-Indigenous anthropogenic speculative climate change novels fall into. Likewise, it posits that the novel, unlike many non-indigenous novels, scales in and out of space, time and matter throughout the narrative without disrupting the frame: hence, as the planet requires, the text itself is adaptable to the scales of the past, present and future anthropocene and the speculative futures they invoke.